Effect of hypoxia on the response of canine mammary gland tumor cells to bovine lactoferrin, doxorubucin and recombinant human erythropoietin - Tan, Felina Peck Yen; How, Chee Wun; Teo, Guan Young; Abdullah, Rasedee (2010)
The exact role of hypoxia in tumor biology remains controversial because there is no conclusive evident on its effect on tumors. There is concern that tumor hypoxia is one of the causes of chemoresistance in cancer cells. Recently, erythropoietin receptors have been found in human breast cancer cells indicating that recombinant human erythropoietin (rHuEPO) treatment of cancer-related anemia can influence the functions of the cells. Bovine lactoferrin (bLF) was also shown to have antiproliferative effects on cancer cells. The aim of this study was to determine the in vitro effects of rHuEPO, bLF and Doxorubicin (DOX) on a canine mammary gland tumor cell line, CMT-stylo cells, under hypoxic condition. The cells were treated with bLF, rHuEPO, DOX rHuEPO and DOX and bLF, rHuEPO combinations. These treated cells were subjected to MTT assay. The results showed that hypoxia lowered the proliferation rate of the CMT-stylo cells while combination treatments showed improved killing. Flow cytometry analysis showed that DOX had cytotoxic while bLF had antiproliferative effects on the CMT-stylo cells.